Penyidikan Tindak Pidana Pelecehan Seksual Pada Ruang Publik (Street Harassment) Di Polda Jakarta (RechtJiva, 2024)
The cases of street harassment are increasing with women as victims, causing humiliation and traumatic conditions. Public places such as commuter lines are the common places where street harassment often happens. Departing from this issue, this research seeks to investigate the mechanism of the enquiry into street harassment cases in the Regional Police Department of Jakarta Raya and the impeding factors faced by the police and the commuter line company regarding street harassment in the commuter line. Combining doctrinal and empirical research methods, this research has found that the enquiry following the report made on the case involves report submission, investigation, witness investigation, deciding the defendant, evidence collection, and filing. The commuter line company has received reports, conducted coordination with the police department, and transferred the perpetrator to the police when the victim wishes to proceed with the report. However, the police department has been facing issues in discovering information from the victim due to stigma. Another issue faced by the commuter line company is that most victims choose not to proceed with the report and prefer posting the problems on social media, and this trend seems to present another problem for the authorities concerned. The Regional Police Department of Jakarta Raya has taken preventive and repressive actions by giving further introduction and strict measures against the perpetrators. Departing from this issue, the commuter company initiated to provide special train cars for women and a 5D method.